Reliability and Quality of Complex Systems - D.N. Novomeisky; M.N. Piganov; E.T. Eskibaev (Надежность и качество сложных систем)
Background. The relevance of the topic of this work is due to the need to improve the efficiency, reliability and quality of measurement control results during electrophysical processing of film resistors of microassemblies by high-frequency flare discharge. Purpose – Analysis and evaluation of methodological errors in the process of electrophysical processing of film resistors by high-frequency flare discharge, implemented according to a given algorithm. Materials and methods. Computer modeling, programming, full-scale experiment, expert assessments were used. A systematic analysis of errors in the electrophysical processing of film resistors by high-frequency flare discharge is carried out. He showed that the main contribution to the accuracy characteristics of the technological processing device is made by the elements of methodological, instrumental and additional errors. The main components of the methodological error are revealed. It is shown that among the elements of the general methodological error, the error of the gap between the film resistor and the working electrode of the processing device is of decisive importance. When determining the size of the gap between the electrode and the film, the formula included in the flare discharge treatment model was used. The MathCAD mathematical package was used for calculations. A detailed analysis of the process of formation of the methodological error in determining the gap between the electrode and the film during the operation of the technological device showed that the main factors of its formation are the power and temperature of the torch acting on the surface of the sample. The estimation of the methodological error of the gap "resistor-electrode" is carried out. Results. Mathematical expressions for determining the methodological error are obtained. The general methodological error in determining the gap size for the worst case is 20 %. When estimating the error in determining the temperature of the torch, the method of "rectangles" was used. He showed that the methodological error in determining the discharge temperature is 2,6 %. Conclusions. These results can be used when selecting the measuring part of the flare discharge processing control device, in the process of optimizing measurement procedures, as well as as input data for the development of an AIS for technological support of the processing of film structures.